EFFECT OF SQUID POWDER (LOLIGO SP.) ON ANTIBODY TITER AND BACTERIA DENSITY IN BLOOD OF TILAPIA (OREOCHROMIS NILOTICUS) INFECTED BY AEROMONAS HYDROPHILA. - Fadjar, Mohamad; Sanoesi, Ellana; Mintiya, Yoga Aris; Hakim, Lukmanul (Aquacultura Indonesiana, 2020)
Aeromonas hydrophila is bacteria that often infect freshwater fish and causes Motile Aeromonas Septicemia (MAS) disease. One alternative antibacterial that can be used is squid ink (Loligo sp.) which contains antibacterial substances. The purpose of this study was to determine the effect of squid ink (Loligo sp.) on antibody titers and bacterial density in tilapia infected with A. hydrophila.This study used a Completely Randomized Design (CRD) with the treatment of squid ink powder in feed at a dose of 52.5 ppm (A), 62.5 ppm (B) and 72.5 ppm (C), positive control (K+) using oxytetracycline ( 20 ppm) on feed and negative control (K-) without giving treatment to feed. The main parameters observed were bacterial density in blood of tilapia (O. niloticus) and antibody titer. In addition to the main parameters, supporting parameters observed in this study included survival rate (SR), and measurements of water quality (temperature, DO and pH).      The best dose in giving squid ink (Loligo sp.) powder in feed was 62.5 ppm (treatment B) because it supresing bacterial density in the blood of tilapia (O. niloticus) until 166.33 X 103 cfu/mL, decreasing antibody titer from 26.67±09.24 % to 13.00±04.62 % and highest survival rate of 90.47%.